Intraneural perineurioma of the brachial plexus [Braki̇yal pleksusun i̇ntranöral peri̇nöromasi] - (:unkn) unknown (My University, 2010)
Intraneural perineurioma (IP) is a rare and slowly progressing disease which is characterized by spindled perineurial cells, arranged in pseudo-onion bulb whorls around one or more centrally situated Schwann cells. Diagnosis of the disease is based mainly on histologic findings and immunohistochemical profile. Although cytogenetic and molecular genetic studies are of limited value, they may play an important role in the differential diagnosis of the IP, with many other overlapping soft tissue tumors.
Keywords: Brachial plexus; Intraneural perineuroma; Tumour